Bioactive Components of Pomegranate Oil and Their Influence on Mycotoxin Secretion - Badr, Ahmed Noah (Toxins (Basel), 2020)
Pomegranate, similar to other fruits, has juice-extraction by-products. Pomegranate seed oil (PGO) is a non-traditional oil with health benefits, rich in bioactive components. This study was aimed to assess PGO phytochemicals and their influence as bioactive components to reduce mycotoxin secretion. The encapsulation was applied in micro and nanoforms to protect the quality and enhance the efficacy of the oil. The PGO was extracted using ultrasound-assisted methods. Carotenoids, tocochromanols, sterols, phenolic, flavonoid, antioxidant, and antimicrobial activity were determined. The fatty acid profile was analyzed by the GC-MS, while mycotoxin was determined utilizing the HPLC apparatus. The toxicity and protective action of oil were examined using the hepatocytes’ cell line. The resultant oil acts as oleoresin that is rich in bioactive molecules. Phenolics and antioxidant potency recorded higher values compared to traditional vegetable oils, whereas polyunsaturated fatty acids were 87.51%. The major fatty acid was conjugated punicic acid (81.29%), which has high biological effects. Application of the PGO on fungal media reduced aflatoxins secretion up to 63%, and zearalenone up to 78.5%. These results confirm the bio-functionality of oil to regulate the fungal secondary metabolites process. The PGO is a unique prospective non-traditional oil and has several functionalities in food, which achieve nutritional, antioxidant, and anti-mycotoxigenic activities.